Under ice habitats for Antarctic krill larvae: Could less mean more under climate warming?. Issue 19 (15th October 2016) - Melbourne‐Thomas, J.; Corney, S. P.; Trebilco, R.; Meiners, K. M.; Stevens, R. P.; Kawaguchi, S.; Sumner, M. D.; Constable, A. J.
Abstract: Overwintering of larvae underneath Antarctic pack ice is a critical stage in the life cycle of Antarctic krill. However, there are no circumpolar assessments of available habitat for larval krill, making it difficult to evaluate how climate change may impact this life stage. We use outputs from a circumpolar sea ice model, together with a set of simple assumptions regarding key habitat features, to identify possible regions of larval krill habitat around Antarctica during winter. We assume that the location and suitability of habitat is determined by both food availability and three‐dimensional complexity of the sea ice. A comparison of the combined area of these regions under current conditions with a warm climate scenario indicates that while total areal sea ice extent decreases, there is a consistently larger area of potential larval krill habitat under warm conditions. These findings suggest that decreases in sea ice extent may not necessarily be detrimental for krill populations. Key Points: Outputs from a sea ice model are used to identify potential habitat for Antarctic krill larvae Model results indicate that the area of larval krill habitat may increase under climate change Processes affecting different krill life stages under future scenarios require further consideration